Predicting of Parameters Affecting on PE Wax Powder Size Distribution and Shape in Atomization Process - Madua, Ubonwan; Prasertsit, Kulchanat; Innachitra, Paiboon; Keatkhunboot, Tanakorn (ASEAN Journal of Chemical Engineering, 2013)
The aim of this work is to study the parameters affecting on the particle size distribution and shape of Polyethylene wax (PE wax) powders in atomization process. Effect of liquid flow rate, melting temperature and air pressure are studied parameters. External mixing two fluid nozzles is used and temperature is controlled at 200˚C to avoid freeze-up within the liquid cap. PE wax is melted at various temperatures from 120˚C to 180˚C and is atomized with air pressures from 1 to 7 bar. Particle size and size distribution are determined by Particle Sizing Unified System (Mastersizer, 2000). Using 1 bar of air pressure, 140˚C of melting temperature and 3.0:1.5 of ALR gives the PE wax powders size that smaller than 200 micron and high bulk density. Moreover, smoothly and silky surface of PE wax powders are obtained.